A silicon carbide wafer and a method of manufacturing the same

CN121931603BActive Publication Date: 2026-10-09CHENGDU ZHONGWEI CRYSTAL MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610137701.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-30
Publication Date
2026-10-09
Estimated Expiration
2046-01-30

AI Technical Summary

Technical Problem

石墨纸/碳毡填充法采用机械夹具施加压力固定,虽然工艺简单且成本较低,但在热接触均匀性和压力控制方面存在不足,存在填充物引入杂质的风险,且在制备大尺寸单晶方面难以维持压力的均匀性;石墨膏/碳基浆料涂层法通过烧结形成碳质粘接层,能实现更紧密的热接触和应力分布,是目前工业界最广泛采用的技术,但是该技术仍存在缺陷,如浆料烧结后仍是异质层,其热膨胀系数与SiC/C不完全匹配,热应力问题依然存在;浆料成分、涂覆厚度、干燥/烧结工艺对最终性能影响大,需要严格控制;可能引入碳杂质;因粘接牢固,拆卸生长后的晶体可能更困难;有机溶剂处理需要安全措施

Benefits of technology

本发明在碳化硅晶圆的制备过程中,提供原位反应构建成分梯度的(Ti,Si)C固溶体过渡层,有效解决了石墨/SiC物性突变难题;激光熔覆后,焊接一起的碳化硅籽晶与石墨基底的焊接强度(>150MPa,220℃不衰减)远高于传统胶粘(粘接强度<10MPa),能承受晶体生长过程中剧烈的热冲击、旋转离心力、晶体自重等。该工艺最大限度地保护了籽晶的完整性,避免了因连接应力导致的籽晶开裂或生长晶体质量下降。在制备过程中无污染源,有效消除了有机胶粘剂带来的污染源,提高晶体纯度和生长成功率,延长晶体生长设备的使用寿命。数字化控制的激光参数和精确定位确保了每个焊点的质量高度一致,重复性好,良率高。从根本上解决了因焊接问题导致的籽晶脱落、位错引入等问题,是生长大尺寸、低缺陷、高品质单晶的关键保障之一。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121931603B_ABST
    Figure CN121931603B_ABST
Patent Text Reader

Abstract

The application discloses a silicon carbide wafer and a preparation method thereof, and relates to the technical field of semiconductors. The preparation of the silicon carbide wafer comprises a raw material and seed crystal preparation stage and a crystal growth stage; wherein the raw material and seed crystal preparation stage adopts laser to melt a Ti foil at high temperature, and welds a silicon carbide seed crystal on the surface of a graphite base, the welding strength is much higher than that of traditional glue sticking, and the problem of sudden change of the physical properties of the graphite / SiC is solved. The integrity of the seed crystal is maximally protected, and the seed crystal cracking or crystal quality reduction caused by connection stress is avoided. The preparation process eliminates the pollution source caused by the organic glue sticking agent, improves the crystal purity and growth efficiency, and prolongs the service life of the crystal growth equipment. The digital control laser parameters and accurate positioning ensure that the quality of each welding point is highly consistent, has good repeatability, and has high yield. The problems of seed crystal falling off and dislocation introduction caused by the welding problem are fundamentally solved, and the method is one of key guarantees for growing large-size, low-defect and high-quality single crystals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor technology, and more specifically, to a silicon carbide wafer and a method for preparing the same. Background Technology

[0002] Silicon carbide (SiC) single crystals, due to their excellent physical and chemical properties, such as high bandgap, high thermal conductivity, and high breakdown electric field, have become a key substrate material for next-generation power semiconductor devices. Physical vapor transport (PVT) is currently the mainstream method for the industrial production of SiC single crystals, and its growth process requires a high-temperature environment above 2000°C. As a crucial pretreatment step in the PVT growth process, the quality of the seed crystal bonding technology directly affects the success or failure of crystal growth and the final quality. During the PVT growth of SiC single crystals, the seed crystal needs to be precisely fixed on the graphite crucible cap (seed crystal holder) and meet three core requirements: firm mechanical fixation, good thermal conductivity, and stability under high-temperature conditions.

[0003] Currently, the mainstream seed crystal bonding technologies mainly include two methods: graphite paper / carbon felt filling and graphite paste / carbon-based slurry coating. The graphite paper / carbon felt filling method uses mechanical clamps to apply pressure for fixation. Although the process is simple and low-cost, it has shortcomings in terms of thermal contact uniformity and pressure control, carries the risk of introducing impurities into the filler, and is difficult to maintain pressure uniformity when preparing large-size single crystals. The graphite paste / carbon-based slurry coating method forms a carbonaceous bonding layer through sintering, achieving tighter thermal contact and stress distribution. It is currently the most widely used technology in industry, but this technology still has drawbacks. For example, the slurry remains a heterogeneous layer after sintering, and its coefficient of thermal expansion does not perfectly match that of SiC / C, so thermal stress problems still exist. The slurry composition, coating thickness, and drying / sintering process have a significant impact on the final performance and require strict control. It may introduce carbon impurities. Due to the strong adhesion, disassembling the grown crystal may be more difficult. Organic solvent handling requires safety measures.

[0004] While these two technologies have matured relatively quickly through long-term practice, they still face several key challenges. The most prominent is the mismatch in thermal expansion coefficients: SiC's thermal expansion coefficient is much lower than that of graphite. This difference generates significant thermal stress during heating and cooling, leading to seed crystal warping, cracking, and even detachment. Furthermore, controlling the consistency of the bonding interface quality is difficult, including the formation of voids and defects, the introduction of trace impurities, and the precise control of bonding strength and thickness. These problems are particularly pronounced in large-size wafer production, becoming major bottlenecks limiting yield improvement and further breakthroughs in crystal quality. In addition, uniformity, consistency, impurity control, stringent surface requirements, and process dependence are also significant challenges.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a silicon carbide wafer and a method for preparing the same, so as to solve or improve the above-mentioned technical problems.

[0007] This invention is implemented as follows: In a first aspect, the present invention provides a method for preparing a silicon carbide wafer, comprising the following steps: a raw material and seed crystal preparation stage and a crystal growth stage; The raw material and seed crystal preparation stage includes using a laser with a power of 300W-500W, a spot diameter of 0.1mm-1.5mm, and a scanning speed of 2mm / s-10mm / s to weld silicon carbide seed crystals onto the surface of a graphite substrate.

[0008] In an optional implementation, the laser power is 300W-400W, the spot diameter is 0.5mm-1.2mm, and the scanning speed is 2mm / s-5mm / s; And / or, the wavelength of the laser is 1050nm-1070nm.

[0009] In an optional embodiment, a layer of titanium foil is further placed between the silicon carbide seed crystal and the graphite substrate; The thickness of the titanium foil is 20μm-50μm.

[0010] In an optional embodiment, the thickness of the titanium foil is 20 μm-30 μm.

[0011] In an optional implementation, the raw material and seed crystal preparation stage further includes: The pre-welded surface of the graphite substrate was polished to Ra < 0.1 μm; And / or, after soaking the silicon carbide seed crystal in hydrofluoric acid with a concentration of 5 wt%-10 wt%, it is washed with water and then dried. And / or, clean the surface of the titanium foil with an alcohol solvent; And / or, seed welding is performed in a protective atmosphere; wherein the flow rate of the protective atmosphere is 15 L / min-20 L / min, and the protective atmosphere is selected from at least one of argon and helium.

[0012] In an optional embodiment, the raw material and seed crystal preparation stage further includes pressurizing the silicon carbide seed crystal, titanium foil and graphite substrate at a pressure of 0.5 MPa-1 MPa. And / or, after the seed crystal welding is completed and the laser is removed, the welded seed crystal system is cooled to 600℃-800℃ at a rate of 5℃ / s-10℃ / s.

[0013] In an optional embodiment, the bonding strength between the welded silicon carbide seed crystal and the graphite substrate is >150 MPa. And / or, a solid solution transition layer with a thickness of 15μm-25μm is formed between the welded silicon carbide seed crystal and the graphite substrate.

[0014] In an optional implementation, the crystal growth stage includes the following steps: After loading the powder and seed crystals into the crucible, seal the furnace body and evacuate to a vacuum level of <10. -3 After Pa, the temperature is raised to 1500℃-1800℃ and held for 1-2 hours; then the temperature is raised to 2000℃-2200℃, with an axial temperature gradient ΔT=15℃ / cm-30℃ / cm; the powder is 4H-SiC silicon carbide powder. Crystals were continuously epitaxially grown at temperatures of 2100℃-2400℃, growth rates of 0.1 mm / h-1 mm / h, and nitrogen flow rates of 10 sccm-200 sccm. During this period, the crystal growth gas pressure was controlled in a low-pressure mode of 1 kPa-10 kPa and a high-pressure mode of 10 kPa-100 kPa. After growth, the temperature is reduced at a rate of 30℃ / h - 50℃ / h and cooled to room temperature in a protective atmosphere; the protective atmosphere is selected from argon or helium.

[0015] In an optional embodiment, the preparation method further includes an equipment preparation stage; The equipment used includes: a high-temperature induction furnace, a crucible made of high-purity graphite, a heat insulation layer made of carbon felt / graphite felt composite material, and a vacuum device consisting of mechanical pumps and molecular pumps.

[0016] Secondly, the present invention provides a silicon carbide wafer, which is prepared by any of the preparation methods described in the foregoing embodiments, and no abnormalities such as seed crystal backing, edge ablation, full-surface pitting, and chipping occur during the growth of the silicon carbide wafer.

[0017] The present invention has the following beneficial effects: This invention provides an in-situ reaction to construct a (Ti,Si)C solid solution transition layer with a compositional gradient during the fabrication of silicon carbide wafers, effectively solving the problem of abrupt property changes in graphite / SiC. After laser cladding, the weld strength (>150MPa, no attenuation at 220℃) between the welded silicon carbide seed and the graphite substrate is far higher than that of traditional adhesive bonding (bonding strength <10MPa), and can withstand the severe thermal shock, centrifugal force, and crystal weight during crystal growth. This process maximizes the protection of the seed's integrity, avoiding seed cracking or quality degradation caused by bonding stress. The fabrication process is pollution-free, effectively eliminating contamination from organic adhesives, improving crystal purity and growth success rate, and extending the lifespan of crystal growth equipment. Digitally controlled laser parameters and precise positioning ensure high consistency, repeatability, and high yield of each weld point. It fundamentally solves problems such as seed detachment and dislocation introduction caused by welding issues, and is one of the key guarantees for growing large-size, low-defect, high-quality single crystals. Attached Figure Description

[0018] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 Morphology analysis of different products in Example 1: (a) Morphology of the silicon carbide seed crystal after welding; (b) Partial magnified view of the silicon carbide seed crystal after welding; (c) Morphology of the silicon carbide wafer from the first perspective; (d) Morphology of the silicon carbide wafer from the second perspective. Figure 2 For the morphology analysis of different products in Comparative Example 1: (a) Morphology of the bonded silicon carbide seed crystal; (b) Morphology of the obtained silicon carbide wafer. Figure 3 For the morphology analysis of different products in Comparative Example 2: (a) is a morphology diagram of the bonded silicon carbide seed crystal; (b) is a morphology diagram of the obtained silicon carbide wafer. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0021] In a first aspect, the present invention provides a method for preparing a silicon carbide wafer, comprising the following steps: a raw material and seed crystal preparation stage and a crystal growth stage; The raw material and seed crystal preparation stage includes using a laser with a power of 300W-500W, a spot diameter of 0.1mm-1.5mm, and a scanning speed of 2mm / s-10mm / s to weld silicon carbide seed crystals onto the surface of a graphite substrate.

[0022] The laser is used to melt titanium (Ti) foil, and the power is controlled to avoid excessive heat input; the set spot diameter can effectively cover the width of the titanium foil, making the heating uniform; the setting of the scanning speed is used to control the reaction time and prevent SiC decomposition.

[0023] It should be noted that the silicon carbide wafers in this invention are prepared using the physical vapor transport (PVT) method. The silicon carbide raw material (in powder form) is sublimated by heating at high temperature. Under the drive of the temperature gradient, gaseous substances such as Si, Si2C, and SiC2 are transported to the surface of the silicon carbide seed crystal in the low-temperature region and recrystallized, eventually forming a silicon carbide wafer.

[0024] In an optional implementation, the laser power is 300W-400W, the spot diameter is 0.5mm-1.2mm, and the scanning speed is 2mm / s-5mm / s.

[0025] It should be noted that with a suitable laser power setting, the laser intensity is stable (65MPa-75MPa), the heat-affected zone is small (<200μm), the TiC grains are fine (0.5μm-2μm), the solid solution interface is clear, and the decomposition of SiC is negligible. If the laser power is increased to 400W-500W, the intensity is high (70MPa-85MPa), the heat-affected zone is moderate (200μm-400μm), the TiC layer slightly melts, and the solid solution thickens; the SiC surface undergoes slight sublimation, increasing the risk of silicon loss. If the laser power >500W, SiC decomposes (the intensity drops sharply to 20 MPa), leading to graphite ablation, vaporization pores in SiC, and layered graphite peeling; furthermore, defects such as cracks, pores, and increased sputtering appear on the SiC surface. If the laser power is less than 300 W, the reaction is incomplete. At this time, the laser intensity is less than 50 MPa, resulting in defects such as incomplete fusion of the welding area, incomplete melting of the titanium foil, and island-like distribution of TiC, leading to an area of ​​unbonded SiC exceeding 30%.

[0026] For example, the power of the laser is selected from at least one of 300W, 310W, 330W, 350W, 370W and 400W, or other values ​​in the range of 300W-400W.

[0027] In optional implementations, the set spot diameter needs to cover the width of the titanium foil to ensure uniform heating. The spot diameter affects the uniformity of the Ti melt and the presence of defects such as porosity and ablation on the final SiC surface. When the spot diameter is 0.5mm-1.2mm, the Ti melt is uniform, the TiC layer is continuous with moderate bonding strength, and the amount of porosity is low; the TiC layer thickness needs to be precisely controlled. When the spot diameter is 0.1mm-0.3mm, the Ti melt pool is deep and narrow, the TiC layer is thin but easily discontinuous, and prone to splashing leading to porosity; SiC exhibits ablation / decomposition, microcracks, and Ti evaporation contamination in >80% of the sample area. When the spot diameter is >1.5mm, the titanium foil is not fully melted, the bonding between the silicon carbide seed and the graphite substrate is weak, the TiC layer is thick and brittle; defects such as incomplete fusion and interface delamination exist, and the seed exhibits thermal deformation.

[0028] For example, the spot diameter is selected from at least one of 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1.0mm, 1.1mm and 1.2mm, or other values ​​in the range of 0.5mm-1.2mm.

[0029] Setting the scanning speed controls the reaction time and prevents SiC decomposition. When the scanning speed is 2 mm / s-5 mm / s, the laser intensity is at its peak, ranging from 70 MPa to 85 MPa. At this speed, the reaction between the silicon carbide seed and the titanium foil interface is sufficient, the TiC / solid solution gradient transition is optimized, and defects are near-zero. When the scanning speed is 5 mm / s-10 mm / s, the laser intensity is acceptable, ranging from 50 MPa to 65 MPa. However, the heat input is reduced, the TiC layer is thinner (3 μm-8 μm), and the solid solution is incomplete; the risk of localized incomplete fusion increases. When the scanning speed is <2 mm / s, the silicon carbide seed and graphite substrate overheat, the laser intensity decreases, and the heat-affected zone expands to >500 μm. At this speed, TiC grains grow abnormally, SiC decomposes, cracks appear on the crystal surface, and porosity increases significantly. When the scanning speed is >10 mm / s, the laser intensity is <40 MPa, the reaction is interrupted, and the titanium foil is not completely melted. At this time, TiC is in the form of discrete particles, mainly bonded by interfacial mechanical bonding, and large areas of unbonded defects appear in the crystal.

[0030] For example, the scanning speed is selected from at least one of 2 mm / s, 2.5 mm / s, 3 mm / s, 3.5 mm / s, 4 mm / s and 5 mm / s, or other values ​​in the range of 2 mm / s to 5 mm / s.

[0031] And / or, the wavelength of the laser is 1050nm-1070nm.

[0032] In the optimal implementation, the laser type is a fiber laser with a wavelength of 1064 nm. This wavelength of laser has the characteristics of high absorption rate and good beam quality. Furthermore, digitally controlled laser parameters and precise positioning ensure highly consistent quality, good repeatability, and high yield for each solder joint.

[0033] Laser welding results in a heat-affected zone of less than 200 μm, employing localized heating which helps protect the properties of the base material. Single-pass welding time is less than 10 seconds, and the overall welding time is less than 30 minutes (compared to over ten hours for traditional welding processes). Furthermore, the highly concentrated laser energy generates heat only in the tiny interface areas where connection is required, minimizing the thermal impact on the seed crystal body and the seed crystal rod as a whole. Due to the extremely small heat input area and short duration, thermal deformation and residual stress are effectively controlled to low levels, making it particularly suitable for the growth of high-quality single crystals that are extremely sensitive to thermal and mechanical stresses.

[0034] Laser cladding eliminates the need for chemical adhesives, preventing the volatilization and decomposition of organic pollutants during high-temperature crystal growth, which could contaminate the furnace and crystal. The entire welding process is typically conducted under inert gas protection, generating no harmful fumes (compared to traditional bonding).

[0035] It should be noted that the laser cladding process for silicon carbide seed crystals and graphite substrates provided in this invention can also be used to weld various difficult-to-weld materials (such as sapphire, silicon carbide, YAG, various oxide crystals, etc.) to metal substrates (molybdenum, tungsten, titanium, stainless steel, etc.). This process has significant advantages in high-temperature, high-vacuum, and highly corrosive environments where traditional adhesive bonding and welding are difficult to perform.

[0036] In an optional embodiment, a layer of titanium foil is further placed between the silicon carbide seed crystal and the graphite substrate; The thickness of the titanium foil is 20μm-50μm.

[0037] The presence of titanium foil facilitates in-situ reactions, forming a TiC-SiC solid solution transition layer between the silicon carbide seed and the graphite substrate. This improves the welding strength between the silicon carbide seed and the graphite substrate, promotes the consistency of the welding interface quality, and alleviates thermal stress caused by the mismatch in coefficients of thermal expansion. The CTE of TiC and Ti3SiC2, which is between that of SiC and graphite, can reduce thermal stress, thereby improving the quality and yield of the fabricated silicon carbide wafers. Specifically, the mechanism of the in-situ reaction is divided into stages: First stage: Titanium foil melting (temperature > 1668℃), laser beam scans titanium foil, molten titanium spreads and wets the surface of graphite substrate to form liquid film.

[0038] The second stage: Ti-C reaction (temperature > 1250℃), molten titanium reacts with graphite to form a TiC layer with a thickness of 15μm-25μm. The reaction time is 30 seconds, and the relevant chemical reaction formula is Ti(l) + C(s) → TiC(s).

[0039] The third stage: formation of TiC-SiC solid solution transition layer. Under the action of laser, TiC generated and silicon carbide seed crystal interface undergo atomic interdiffusion to form a (Ti,Si)C solid solution transition layer with a thickness of 15μm-25μm.

[0040] It should be noted that the stability of the TiC (melting point 3140℃) and (Ti,Si)C solid solution transition layer (melting point > 3000℃) is much higher than that of brazing (melting point < 900℃) or adhesive bonding (melting point < 500℃). It is suitable for extreme environments with temperatures > 1600℃ (such as rocket engine nozzles and nuclear reactor inner walls).

[0041] The titanium foil used is high-purity titanium foil. Before use, its surface needs to be wiped with an alcohol solvent to remove surface oil and other contaminants. In this embodiment of the invention, ethanol is used as the alcohol solvent. In other embodiments of the invention, ethylene glycol, propanol, or other alcohol solvents can be used for wiping.

[0042] The thickness of the titanium foil affects the quality of the TiC layer, and consequently the adhesion strength between the silicon carbide seed crystal and the graphite substrate. When the titanium foil thickness is 20μm-30μm, the adhesion strength is optimal, ranging from 60MPa to 80MPa; the TiC layer is uniform, with a thickness of 15μm-25μm; the resulting TiC layer is dense, the (Ti,Si)C solid solution transition layer is continuous, thermal stress is controllable, and the crack risk is low. When the titanium foil thickness is 30μm-40μm, the adhesion strength is moderate, ranging from 50MPa to 70MPa, with slightly higher residual stress; the TiC layer thickens to 40μm-50μm; defects such as discontinuities in the solid solution appear; and the probability of interfacial microcracks due to differences in cooling shrinkage increases. When the titanium foil thickness is <20μm, the adhesion strength is insufficient, below 40MPa; the reaction layer is discontinuous and TiC does not cover the entire interface; unreacted titanium regions exist, increasing the risk of interfacial delamination. When the thickness of the titanium foil is >50 μm, the bonding strength fluctuates greatly, ranging from 30 MPa to 60 MPa. At this point, the heat input requirement is high, resulting in residual titanium aggregation, porous defects in the TiC layer, and increased interlayer cracking.

[0043] In an optional embodiment, the thickness of the titanium foil is 20 μm-30 μm.

[0044] For example, the thickness of the titanium foil is selected from at least one of 20 μm, 22 μm, 23 μm, 25 μm, 28 μm and 30 μm, or other values ​​in the range of 20 μm to 30 μm.

[0045] In an optional implementation, the raw material and seed crystal preparation stage further includes: The pre-welded surface of the graphite substrate was polished to Ra < 0.1 μm; then, the organic matter on the surface of the graphite substrate was removed by ultrasonic cleaning with acetone.

[0046] And / or, the silicon carbide seed crystal is immersed in hydrofluoric acid with a concentration of 5wt%-10wt%, then cleaned with water, and finally dried. The hydrofluoric acid is mainly used to remove the oxide layer and damaged layer on the surface of the silicon carbide seed crystal. The water used for cleaning can be deionized water, ultrapure water, or distilled water, depending on the needs. Vacuum drying is used, and the drying temperature and time are not particularly limited and can be adjusted reasonably according to actual needs. In this embodiment of the invention, the drying temperature is 70℃ and the drying time is 4 hours.

[0047] And / or, clean the surface of the titanium foil with an alcohol solvent to ensure that the surface of the titanium foil is clean and free of contaminants.

[0048] And / or, seed crystal welding is performed in a protective atmosphere; wherein the flow rate of the protective atmosphere is 15 L / min-20 L / min, and the protective atmosphere is selected from at least one of argon and helium. Performing the welding in a protective atmosphere helps to prevent oxidation of titanium / silicon carbide.

[0049] In an optional implementation, the raw material and seed crystal preparation stage further includes pressurizing the silicon carbide seed crystal, titanium foil, and graphite substrate at a pressure of 0.5 MPa-1 MPa; specifically, the graphite substrate, titanium foil, and silicon carbide seed crystal are stacked in the order of graphite substrate → titanium foil → silicon carbide seed crystal, and a pressure of 0.5 MPa-1 MPa is applied to ensure tight contact at the interface.

[0050] And / or, after the seed crystal welding is completed and the laser is removed, the welded seed crystal system is cooled to 600℃-800℃ at a rate of 5℃ / s-10℃ / s, which can effectively avoid thermal stress cracking of silicon carbide wafers.

[0051] In an optional implementation, the welded silicon carbide seed crystal and graphite substrate need to be cooled to room temperature under vacuum conditions; And / or, a solid solution transition layer with a thickness of 15μm-25μm is formed between the welded silicon carbide seed crystal and the graphite substrate.

[0052] In an optional implementation, the crystal growth stage includes the following steps: After loading the powder and seed crystals into the crucible, seal the furnace body and evacuate to a vacuum level of <10. -3After Pa, the temperature is raised to 1500℃-1800℃ and held for 1-2 hours; then the temperature is raised to 2000℃-2200℃, with an axial temperature gradient ΔT = 15℃ / cm-30℃ / cm; the powder is 4H-SiC silicon carbide powder. Vacuuming is to prevent oxidation and reduce the introduction of gaseous impurities; the holding treatment at 1500℃-1800℃ is a high-temperature purification stage, which is to further degas and remove adsorbed gases and volatile impurities; the temperature is then raised to 2000℃-2200℃ to enter the initial growth stage, at which point the sublimation-transport process is initiated, an axial temperature gradient is established, the uniformity of radial growth is controlled, and the temperature deviation is kept less than 5℃.

[0053] Under conditions of 2100℃-2400℃, a growth rate of 0.1 mm / h-1 mm / h, and a nitrogen flow rate of 10 sccm-200 sccm, continuous epitaxial growth of the crystal was achieved. During this period, the crystal growth gas pressure was controlled in a low-pressure mode of 1 kPa-10 kPa and a high-pressure mode of 10 kPa-100 kPa. The temperature of the core growth region was maintained at 2100℃-2400℃ to promote steady-state growth of the silicon carbide wafer. Control of the growth rate and nitrogen flow rate ensured continuous epitaxial growth of the crystal. In addition to serving as a protective gas, N2 also acted as an n-type dopant to adjust the electrical properties of SiC.

[0054] Different modes of controlling the crystal growth gas pressure during the process are beneficial for controlling the crystal growth rate, quality and defect type to adapt to different production objectives.

[0055] In low-pressure mode, the gas phase molecules have a long mean free path and a large diffusion coefficient, resulting in a very fast mass transport rate from the raw material region to the seed crystal region, which can achieve a high crystal growth rate. The low-pressure environment helps control the gas phase stoichiometry near the growth interface, which is beneficial for suppressing the formation of certain macroscopic defects (such as inclusions and polytype inclusions). Low-pressure mode is crucial for the production of conductive SiC substrates (mainly used for power devices) that require large-volume, low-cost production, and can significantly improve production capacity and economic efficiency. However, it also carries the risk of poor thermodynamic stability and surface morphology deterioration.

[0056] In high-pressure mode, the higher pressure enhances natural convection within the cavity, resulting in a more uniform and gentler thermal distribution. The gentler temperature gradient makes the growth interface (solid-gas interface) very stable, approaching the ideal "layered growth" mode, which effectively suppresses dislocations. The grown crystals have lower defect density and better uniformity, as well as good surface morphology, meeting the stringent material quality requirements of high-end devices. However, it suffers from drawbacks such as a lower growth rate and more complex process control.

[0057] Specifically, in the embodiments of the present invention, the low-pressure mode for controlling the crystal growth gas pressure is 1kPa-10kPa, and the high-pressure mode is 10kPa-100kPa; in other embodiments of the present invention, the pressure values ​​required for the specific low-pressure mode and high-pressure mode are reasonably adjusted according to actual needs.

[0058] After growth, the material is cooled to room temperature at a rate of 30℃ / h - 50℃ / h under a protective atmosphere selected from argon or helium. This cooling annealing after growth, with its slow cooling process, helps release thermal stress and reduce crystal defects.

[0059] In an optional embodiment, the preparation method further includes an equipment preparation stage and a post-processing stage; The equipment used includes: a high-temperature induction furnace, a crucible made of high-purity graphite, a heat insulation layer made of carbon felt / graphite felt composite material, and a vacuum device consisting of mechanical pumps and molecular pumps; The post-processing stage includes directional cutting, grinding, polishing and cleaning of the silicon carbide wafer obtained in the crystal growth stage.

[0060] Among them, the high-temperature induction furnace is the growth furnace body for crystal growth; before the silicon carbide wafer, the silicon carbide wafer needs to be welded on the top of the crucible and silicon carbide powder is placed at the bottom of the crucible; the heat insulation layer is mainly to control the thermal field of the growth furnace body and promote the uniform distribution of the thermal field inside the furnace body; the vacuum equipment is to provide a vacuum field.

[0061] Secondly, the present invention provides a silicon carbide wafer prepared by any of the aforementioned embodiments, wherein no abnormalities such as back and edge ablation and drop of seed crystals occur during the growth of the silicon carbide wafer.

[0062] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0063] Example 1 This embodiment provides a silicon carbide wafer, the preparation of which includes the following steps: (1) Equipment preparation stage The growth furnace body is a high-temperature resistant induction furnace; the crucible is made of high-purity graphite, and a silicon carbide seed crystal needs to be welded to the top, while silicon carbide powder needs to be placed at the bottom. The seed crystal and the powder are homogeneous, and the silicon carbide powder is 4H-SiC silicon carbide powder with a purity >99.9995%; the heat insulation layer is a carbon felt / graphite felt composite material; the vacuum equipment consists of a mechanical pump and a molecular pump.

[0064] (2) Raw material and seed crystal preparation stage The graphite substrate, titanium foil, and silicon carbide seed crystal are stacked in that order, and a pressure of 0.8 MPa is applied to ensure tight contact at the interface. Then, they are welded together using a laser.

[0065] The graphite substrate has a pre-welded surface, which is the top of the inner side of the crucible, in contact with the titanium foil. The titanium foil has a thickness of 25 μm. The laser type is a fiber laser with a wavelength of 1064 nm, a power of 360 W, a spot diameter of 0.8 mm, and a scanning speed of 4 mm / s.

[0066] It should be noted that before stacking, the pre-welded surface of the graphite substrate is polished to Ra<0.1μm, and then ultrasonically cleaned with acetone to remove organic matter from the surface of the graphite substrate; the surface of the titanium foil is cleaned with anhydrous ethanol to ensure that the surface of the titanium foil is clean and free of contaminants; the silicon carbide seed crystal is immersed in 6.5wt% hydrofluoric acid to remove the oxide layer on the surface of the seed crystal, and then cleaned with ultrapure water. Finally, it is dried, and then the treated graphite substrate, titanium foil and silicon carbide seed crystal are stacked together.

[0067] (3) Crystal growth stage Loading and Vacuuming: After loading 4H-SiC silicon carbide powder into the bottom of the crucible and the silicon carbide seed crystal welded in step (2) into the crucible, seal the furnace body and evacuate to a vacuum degree <10. -3 Pa eliminates oxidation and reduces gaseous impurities; High-temperature purification: Heat to 1650℃ and hold for 1.5 hours to further degas and remove adsorbed gases and volatile impurities.

[0068] Early growth stage: Initiate the sublimation-transfer process, raise the temperature to 2000℃, with an axial temperature gradient ΔT = 18℃ / cm, and maintain the temperature deviation less than 5℃.

[0069] Steady-state growth: Crystals were continuously epitaxially grown at a temperature of 2200℃, a growth rate of 0.45 mm / h, and a nitrogen flow rate of 130 sccm; the pressure in the low-pressure mode was 5 kPa, and the pressure in the high-pressure mode was 60 kPa.

[0070] Cooling annealing: After growth, the silicon carbide wafer is cooled to room temperature in an argon atmosphere at a rate of 38℃ / h to obtain silicon carbide wafers.

[0071] (4) Post-processing stage The silicon carbide wafer obtained in step (3) is subjected to directional cutting, grinding, polishing and cleaning to obtain a silicon carbide wafer.

[0072] Experimental Example 1 This experimental example is used to study the effect of different laser powers on the fabrication of silicon carbide wafers. The fabrication steps are the same as in Example 1, with the only difference being: (2) Raw material and seed crystal preparation stage The laser power was set to 250W, 360W, 440W and 560W respectively. The welding effect, microstructure and risks of silicon carbide seed crystal and graphite substrate under different laser power are summarized in Table 1.

[0073] Table 1. Data from studies on different laser powers

[0074] Experiment Example 2 This experimental example is used to study the effect of different laser spot diameters on the fabrication of silicon carbide wafers. The fabrication steps are the same as in Example 1, with the only difference being: (2) Raw material and seed crystal preparation stage Different laser spot diameters were set to 0.2 mm, 0.8 mm, 1.0 mm and 1.8 mm, respectively. The welding effect and risks of silicon carbide seed crystal and graphite substrate under different spot diameters are summarized in Table 2.

[0075] Table 2. Data on different spot diameters

[0076] Experimental Example 3 This experimental example is used to study the effect of titanium foil thickness on the preparation of silicon carbide wafers. The preparation steps are the same as in Example 1, with the only difference being: (2) Raw material and seed crystal preparation stage The thicknesses of the titanium foil were set to 15μm, 25μm, 35μm and 50μm, respectively. The welding effect, microstructure and risks of silicon carbide seed crystals to graphite substrates under different titanium foil thicknesses are summarized in Table 3.

[0077] Table 3. Data from studies on different titanium foil thicknesses

[0078] Experiment Example 4 This experimental example is used to study the effect of laser scanning speed on the fabrication of silicon carbide wafers. The fabrication steps are the same as in Example 1, with the only difference being: (2) Raw material and seed crystal preparation stage The laser scanning speeds were set to 1 mm / s, 2.5 mm / s, 4 mm / s and 7 mm / s respectively. The welding effect, microstructure and risks of silicon carbide seed crystal and graphite substrate under different laser scanning speeds are summarized in Table 4.

[0079]

[0080] Table 4. Data from different scanning speeds Comparative Example 1 This comparative example provides a silicon carbide wafer, the preparation of which includes the following steps: (1) Surface treatment Silicon carbide seed crystal: polished on both sides to Ra < 0.5 nm; Ultrasonic cleaning: Clean with acetone, ethanol and deionized water in sequence until the surface of the silicon carbide seed crystal is clean; Graphite base: Turn flat and clean surface dust.

[0081] (2) Cutting graphite paper Cut the graphite paper to the size of the silicon carbide seed crystal, with the diameter of the graphite paper being approximately 0.5 mm larger than the diameter of the seed crystal.

[0082] (3) Pre-lamination Graphite paper is laid flat on the surface of the graphite base, and silicon carbide seed crystal is placed on the upper surface of the graphite paper and lightly pressed to align. AB glue is uniformly coated between the graphite paper and the graphite base, and between the graphite paper and the silicon carbide seed crystal, with a single-sided coating thickness of about 15μm, to facilitate the bonding of the contact surfaces. Then apply a cold press of 0.8 MPa and hold for 3.5 minutes to bond the silicon carbide seed crystal, graphite paper and graphite base together.

[0083] (4) Crystal growth stage The implementation steps and process parameters for this stage are the same as those for the crystal growth stage (3) in Example 1.

[0084] (5) Post-processing stage The implementation steps at this stage are the same as those in (4) crystal growth stage in Example 1.

[0085] Then, the temperature is increased in stages: In the first stage, the temperature is increased from room temperature to 600℃ at a rate of 5℃ / min; In the second stage, the temperature is increased from 600℃ to 1500℃ at a rate of 2℃ / min, held for 30 minutes, and then cooled in the furnace.

[0086] Comparative Example 2 This comparative example provides a silicon carbide wafer whose preparation steps are the same as those in Comparative Example 1, with the only difference being: (3) Pre-lamination The adhesive used to bond graphite paper to the graphite substrate and graphite paper to silicon carbide seed crystals is phenolic resin.

[0087] Test Example 1 In this test example, the morphology of the silicon carbide seed crystal welded in Example 1 and the corresponding silicon carbide wafer, and the silicon carbide seed crystal bonded in Comparative Examples 1-2 and the corresponding silicon carbide wafer, were inspected. The testing method is not limited; visual inspection or microscopic inspection can be used. The test results are shown in […]. Figures 1-3 ;in Figure 1 Morphology analysis of different products in Example 1: (a) Morphology of the silicon carbide seed crystal after welding; (b) Partial magnified view of the silicon carbide seed crystal after welding; (c) Morphology of the silicon carbide wafer from the first perspective; (d) Morphology of the silicon carbide wafer from the second perspective. Figure 2 For the morphology analysis of different products in Comparative Example 1: (a) Morphology of the bonded silicon carbide seed crystal; (b) Morphology of the obtained silicon carbide wafer. Figure 3 For the morphology analysis of different products in Comparative Example 2: (a) is a morphology diagram of the bonded silicon carbide seed crystal; (b) is a morphology diagram of the obtained silicon carbide wafer.

[0088] from Figure 1 It can be seen that 1(a) the overall bonding effect of Ti foil welding is good, the overall welding is uniform, and there are no unwelded areas; 1(b) from the magnified view, the welding texture of Ti foil is uniform and fine, without bubbles; 1(c) the seed crystal welding layer after crystal growth is smooth, and there is no ablation or pitting abnormality on the back, which proves that the bonding layer has good stability during the high temperature process of crystal growth and there is no sublimation phenomenon; 1(d) the front of the ingot is smooth overall, without defects such as phase transformation and microtubes.

[0089] from Figure 2 (a) It can be seen that the AB glue has a better bonding effect in the middle, but more air bubbles at the edges, with an air bubble rate >25%; From Figure 2 (b) It can be seen that the adhesive layer exhibits seed crystal edge ablation and back sublimation during the high-temperature process of crystal growth.

[0090] from Figure 3 (a) It can be seen that the bonding effect of phenolic resin is better than that of AB glue, but the overall glue amount distribution is uneven. Figure 3 (b) It can be seen that during the high-temperature process of crystal growth, there are small pits on the back of the adhesive layer, which is a phenomenon of sublimation on the back of the seed crystal.

[0091] Test Example 2 This test example evaluates the tensile strength of the Ti foil after welding in Example 1, the strength of the AB adhesive bonding in Comparative Example 1, and the strength of the phenolic resin bonding in Comparative Example 2. The test results are summarized in Table 5; and the porosity is also summarized separately. The specific test items and corresponding test methods are as follows: Tensile strength measurement: pull-out force test.

[0092] Porosity: Visually inspected under strong light.

[0093] Table 5 Performance Test Results

[0094] As can be seen from the data in Table 5, the tensile strength of the welding process in Example 1 is much higher than that of the traditional adhesive, and the porosity of the adhesive layer is much lower than that of the traditional adhesive. This indicates that welding can greatly enhance the bonding effect. At the same time, the excellent performance of welding can also reduce the seed crystal abnormality problem during the high-temperature crystal growth process.

[0095] Test Example 3 This test case summarizes the following tests on the silicon carbide seed crystal after Ti foil welding in Example 1 and the silicon carbide seed crystal after AB glue bonding in Comparative Example 1: bonding strength, thermal stress, high temperature stability, thermal conductivity, and the complexity of the preparation process and the defect rate of the obtained silicon carbide wafer. The relevant results are shown in Table 6.

[0096] Table 6 Performance Comparison of Example 1 and Comparative Example 1

[0097] As can be seen from the data in Table 6, the laser micro-fusion welding Ti foil seed crystal bonding technology used in Embodiment 1 of the present invention achieves the following improvements by generating a TiC / Ti gradient solid solution transition layer in situ: High-strength metallurgical bonding: the interface bonding strength is >150MPa, which completely solves the problems of powdering and ablation of the high-temperature bonding layer and ensures zero delamination during the crystal growth process; the bonding ability of the gradient transition layer suppresses the peak thermal stress below 120MPa, avoiding the risk of cracking of SiC in the brittle region of 800℃-1000℃.

[0098] Industrialized and efficient manufacturing: Laser micro-welding takes less than 10 seconds per point and 1 hour for overall welding. It is compatible with batch processing of 6 / 8-inch seed crystals, replacing the traditional time-consuming adhesive curing and cleaning process, reducing overall costs and shortening the working time by 10 times.

[0099] Technical value: This solution not only overcomes the reliability bottleneck of seed crystal bonding in PVT crystal growth, but its composition-structure co-design concept (high thermal conductivity of TiC) also promotes the third-generation semiconductor industry toward large-size, low-defect manufacturing.

[0100] In summary, this invention provides an in-situ reaction to construct a (Ti,Si)C solid solution transition layer with a compositional gradient during the fabrication of silicon carbide wafers, effectively solving the problem of abrupt property changes in graphite / SiC. After laser cladding, the weld strength (>150MPa, no attenuation at 220℃) between the welded silicon carbide seed and the graphite substrate is far higher than that of traditional adhesive bonding (weld strength <10MPa), and can withstand the severe thermal shock, centrifugal force, and crystal weight during crystal growth. This process maximizes the protection of the seed's integrity, avoiding seed cracking or quality degradation due to connection stress. The fabrication process is pollution-free, effectively eliminating contamination from organic adhesives, improving crystal purity and growth success rate, and extending the lifespan of crystal growth equipment. Digitally controlled laser parameters and precise positioning ensure high consistency, repeatability, and high yield of each weld point. It fundamentally solves problems such as seed detachment and dislocation introduction caused by welding issues, and is one of the key guarantees for growing large-size, low-defect, high-quality single crystals.

[0101] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a silicon carbide wafer, characterized in that, The process includes the following steps: raw material and seed crystal preparation stage and crystal growth stage; The raw material and seed crystal preparation stage includes using a laser with a power of 300W-400W, a spot diameter of 0.5mm-1.2mm, and a scanning speed of 2mm / s-5mm / s to weld silicon carbide seed crystals onto the surface of a graphite substrate.

2. The preparation method according to claim 1, characterized in that, The wavelength of the laser is 1050nm-1070nm.

3. The preparation method according to claim 1, characterized in that, There is also a layer of titanium foil between the silicon carbide seed crystal and the graphite substrate; The thickness of the titanium foil is 20μm-50μm.

4. The preparation method according to claim 3, characterized in that, The thickness of the titanium foil is 20μm-30μm.

5. The preparation method according to claim 1, characterized in that, The raw material and seed crystal preparation stage also includes: The pre-welded surface of the graphite substrate was polished to Ra < 0.1 μm; And / or, after soaking the silicon carbide seed crystal in hydrofluoric acid with a concentration of 5wt%-10wt%, it is washed with water and then dried. And / or, clean the surface of the titanium foil with an alcohol solvent; And / or, silicon carbide seed welding is performed in a protective atmosphere; wherein the flow rate of the protective atmosphere is 15 L / min-20 L / min, and the protective atmosphere is selected from at least one of argon and helium.

6. The preparation method according to claim 1, characterized in that, The raw material and seed crystal preparation stage also includes pressurizing the silicon carbide seed crystal, titanium foil and graphite substrate at a pressure of 0.5MPa-1MPa. And / or, after the silicon carbide seed crystal welding is completed and the laser is removed, the welded silicon carbide seed crystal system is further cooled to 600℃-800℃ at a rate of 5℃ / s-10℃ / s.

7. The preparation method according to claim 1, characterized in that, The bonding strength between the welded silicon carbide seed crystal and the graphite substrate is >150MPa; And / or, a solid solution transition layer with a thickness of 15μm-25μm is formed between the welded silicon carbide seed crystal and the graphite substrate.

8. The preparation method according to claim 1, characterized in that, The crystal growth stage includes the following steps: After loading the powder and silicon carbide seed crystal into the crucible, seal the furnace body and evacuate to a vacuum level of <10. -3 After Pa, the temperature is raised to 1500℃-1800℃ and held for 1-2 hours; then the temperature is raised to 2000℃-2200℃, with an axial temperature gradient ΔT=15℃ / cm-30℃ / cm; the powder is 4H-SiC silicon carbide powder. Crystals were continuously epitaxially grown at temperatures of 2100℃-2400℃, growth rates of 0.1 mm / h-1 mm / h, and nitrogen flow rates of 10 sccm-200 sccm. During this period, the crystal growth gas pressure was controlled in a low-pressure mode of 1 kPa-10 kPa and a high-pressure mode of 10 kPa-100 kPa. After growth, the silicon carbide wafer is cooled to room temperature at a rate of 30℃ / h-50℃ / h in a protective atmosphere to obtain silicon carbide wafers; wherein the protective atmosphere is selected from argon or helium.

9. The preparation method according to claim 1, characterized in that, The preparation method also includes an equipment preparation stage and a post-processing stage; The equipment used includes: a high-temperature induction furnace, a crucible made of high-purity graphite, a heat insulation layer made of carbon felt / graphite felt composite material, and a vacuum device consisting of mechanical pumps and molecular pumps; The post-processing stage includes directional cutting, grinding, polishing and cleaning of the silicon carbide wafer obtained in the crystal growth stage.

Citation Information

Patent Citations

  • Preparation device and method based on growth of large-size silicon carbide single crystals

    CN119221104A

  • SiC single crystal block, method for producing SiC single crystal block, and method for producing SiC substrate

    CN119530976A